Indirect FDI under EU FDI regulation in times of war: Is the anti-circumvention clause enough? - Fabrizio Di Benedetto (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
This Perspective explores the consequences of the ECJ decision in the Xella case over the protection of EU security from threats linked to indirect FDI. While the judgement excludes them from the scope of the EU FDI Screening Regulation, this Perspective offers a solution to include them under its scope.
Keywords: 330